PENGARUH ORIENTASI PASAR TERHADAP KINERJA BISNIS: SUATU STUDI PADA INDUSTRI RITEL DENGAN MENGGUNAKAN SKALA MARKET ORIENTATION (MARKOR) - Purwanto Rahardjo; Justine Sirait (Media Riset Bisnis & Manajemen, 2009)
The background of this research "conventional marketing wisdom holds that a market orientation provides a company with a better understanding of its customers, competitors and environment, which subsequently leads to superior business performance. While researchers have explored the relationship between market orientation and business performance in different organizations, such studies in retailers industry are scarce."The objective of this research: "Is there an influence from the market orientation towards business performance of retailers industry?". This research is attempt to test the links among three dimensions of market orientation (intelligence generation, intelligence dissemination and responsiveness) and also the link between market orientation and business performance."Data for this study were collected through personal interviews; and Kohli, Jaworski and Kumar's market orientation scale was used to specify the dimensions of a market-oriented organization. These questions were structured in a Likert Scale model. Because of the size of the sample and number of variables; this research used the Structural Equation Modelling (SEM) analysis."The result of this research conclude that Kohli, Jaworski, and Kumar's market orientation scale provides a good measure of market orientation in this setting. Also the results of analysis indicated a significant link between market orientation and retailers industry performance.Keywords : Market orientation, Intelligence generation, Intelligence dissemination, Responsiveness, Business performance